Eyes that hear. The synesthetic representation of soundspace through architectural photography - Elisa Morselli (Ambiances)
This paper investigates the representation of sound phenomena in contemporary architectural photography. This aspect will be highlighted through a phenomenological analysis conducted on the photographs of the Elbphilharmonie Hamburg, designed by Swiss architecture firm Herzog & de Meuron. Focusing our analysis on the aesthetic features of photographs, the aim of stimulating the audience sensorially and emotionally becomes evident. We usually only focus on visual aspects, neglecting the synesthetic effects generated on the observers. Starting from an analysis of the portrayed persons in terms of expressions, gestures, postures and corporeal directions, the goal is to highlight how they change in relation to the building's sound space, and, as a consequence how they are able to influence the perceiver outside the frame. The interpretation of these clues is based on Herman Schmitz's felt body theory and Gernot Böhme's New Aesthetics.